All Days 2010
DOI: 10.2118/129564-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Water Flooding: Proof Of Wettability Alteration On A Field Wide Scale

Abstract: Summary Low salinity water injection is an emerging EOR technology, applicable to mixed-to-oil-wet sandstone reservoirs. Flooding with low salinity water causes desorption of petroleum heavy ends from the clays present on the pore wall, resulting in a more waterwet rock surface, a lower remaining oil saturation and higher oil recovery. A secondary flood application is discussed in the Omar field in Syria showing a change of wettability from oil wet to a water-wet system. This chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 6 publications
2
65
0
Order By: Relevance
“…In the recent years, extensive laboratory and field tests have showed that LSF can act as an attractive enhanced oil recovery technology [1][2][3][4][5][6]. The popularity of this technology is mainly because of its efficiency in displacing crude oil, low investment, easy operation, ease of injection, and environmental protection, all of which bring economic benefits compared to other chemical EOR methods [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent years, extensive laboratory and field tests have showed that LSF can act as an attractive enhanced oil recovery technology [1][2][3][4][5][6]. The popularity of this technology is mainly because of its efficiency in displacing crude oil, low investment, easy operation, ease of injection, and environmental protection, all of which bring economic benefits compared to other chemical EOR methods [7].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the wettability alteration has been widely believed to be an important contributor to LSF [1,5,7,10]. Wettability alteration of sandstone rocks by LSF is related to the minerals on sandstone surface, the polar components in crude oil and the ion composition of injected water [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced enhanced oil recovery (EOR) techniques are more costly and complex in comparison with water-flooding method. Moreover, low salinity water flooding is emerging as one of the promising recovery methods (Vledder et al, 2010). Advances in technology will enable the maximization of water injection before developing advanced EOR methods (Al-Mutairi and Kokal, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Skauge (2013) identified critical parameters to describe low salinity mechanisms in sandstone such as multi-component ionic exchange, fines migration, wettability alteration, electrical double layer effects, microscopically diverted flow and pH-driven wettability alteration. Dang et al (2013) considered that the most reliable mechanism among these proposed mechanisms is the wettability modification toward a more waterwetting state, as observed by Jadhunandan and Morrow (1995); Tang and Morrow 1999a;Israelachvili (2002, 2004);Vledder et al (2010);and Zekri et al (2011). In addition, ionic exchange among the injected water, the formation water and mineral dissolution/precipitation products in low salinity water can lead to the adsorption of divalent ions and promote mineral dissolution, thereby altering the wettability.…”
mentioning
confidence: 99%